Narrowing of band gap and decrease in dielectric loss in La1-xSrxMnO3 for x = 0.0, 0.1, and 0.2 manganite nanoparticles - Ali, Akhtar; Shah, Wiqar H.; Ullah, Zakir; Malik, Shaheryar; Rauf, Muhammad; Askar, Sameh; Imran, Naveed; Ahmad, Hijaz (Frontiers in Materials, 2024)
Polycrystalline compounds of lanthanum strontium manganite (La1-xSrxMnO3, LSMO) are widely used in electronic storage devices due to their minimal losses and electronic charge transport properties. In this study, we investigated how varying substitutions of Sr2+ for values of x = 0.0, 0.1, and 0.2 affected the tuning of the optical band gap and dielectric losses in La1-xSrxMnO3 nanoparticles. Synthesized samples were structurally analyzed via X-ray diffraction. A rhombohedral R3¯c crystal structure was confirmed for all prepared samples; crystallite size ranging from 15 nm to 20 nm was estimated along with other lattice parameters. Polygonal or hexagonal-like morphology was revealed by field emission scanning electron microscopy, with a moderate size distribution of nanoparticles affected by thinner grain boundaries in doped LSMO. Energy dispersive spectroscopy was employed to confirm the elemental composition of each compound, and the infrared spectrum indicated bonding in the fingerprint region It was observed that there was a significant reduction in the optical band gap, which was measured using ultraviolet spectrometer absorption data. The band gap decreased from 4.34 eV to 4.11 eV. This reduction was found to be related to the difference in refractive index, which was calculated using both Moss and Herve–Vandamme relations. In parallel, frequency-dependent dielectric analysis revealed that frequency was proportional to the increase in Sr content, inversely affecting dielectric loss. Moreover, the AC conductivity of the prepared samples increased with the rise in Sr content, as described by Johnscher’s universal power law in the region of high frequency.